Proceeding of The International Conference Healthcare Systems Day 2024 - (:unkn) unknown (My University, 2024)
The International Conference Healthcare Sytems Day 2024 is organized by the African Working Group in Healthcare Systems, affiliated to AFROS: the African Federation of Operations Research Societies. The Objective of the conference is to bring together OR experts and health professionals – both from the public and private sectors – to develop a network of multidisciplinary skills in the field of health. The event was tailored to appeal to doctors, healthcare managers, researchers, and PhD students with a keen interest in healthcare.The conference has contributed to meet the challenges of this sector through the identification and implementation of action research projects aimed at improving the quality and safety of health services in Africa and around the world. It is by pooling skills and joining forces that this current health situation will be turned around by promoting OR and its applications in healthcare.
Keywords: African Research